Perilaku Prokrastinasi Penyelesaian Study Akhir Mahasiswa Asrama Anjungan Jayawijaya di Kota Jayapura - Kogoya, Yumina; Alberth Reba, Yansen; Mataputun, Yulius (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2023)
The objectives of the present study is to describe the forms of procrastination behavior, the causes of procrastination behavior, and the impact of procrastination behavior on the completion of students' final studies. The researcher applied a qualitative research approach and employed a case study design. The criteria for selecting research subjects included: 1) mastering and understanding the research theme; in this case, students at the Anjungan Jayawijaya dormitory with procrastination behavior towards the completion of their final studies consisting of class 216, 2017 and aged 26, 27 and 29 years. Based on the results of the research, procrastination towards the completion of final studies is generally caused by students' laziness, other activities such as organization and hanging out with friends, and the tendency to play games irresponsibly. Contributing factors include a lack of time management in doing assignments, the priority is focused on earning money for college due to a lack of financial support from parents in supporting education, a lack of self-discipline, a lack of time management, a lack of self-awareness, the influence of involvement in an organization, addiction to playing social media Facebook and the lack of food supply in the dormitory, and the influence of the organization on the subject's personality. The impact of procrastination behavior on the completion of final studies leads to oneself and the environment. The impact on the subject includes shame, anxiety, despair, stress, inferiority, regret, pessimism, loss of appetite, insomnia, loss of enthusiasm for college, low grades.